Studi Awal Perbanyakan Cacao (Theobroma cacao L.) Asal Kebun Rakyat Lombok Utara: Pertumbuhan Bibit pada Media Tanah dengan Pupuk Kandang Sapi - Santoso, Bambang Budi; Ngawit, I Ketut; Jayaputra, Jayaputra (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2024)
Cocoa (Theobroma cacao L.) is an economically valuable crop, especially in the chocolate industry. However, cocoa seedling productivity in Indonesia faces challenges such as low-quality seedlings and suboptimal cultivation practices. This study aimed to evaluate the effect of cow manure on the growth of cocoa seedlings from smallholder farms in North Lombok, focusing on its potential as a sustainable nursery management practice. The experiment was conducted using a randomized complete block design with five treatments involving different ratios of cow manure and standard nursery media (topsoil and sand). Seedling growth parameters such as germination rate, seedling height, stem diameter, leaf number, and biomass accumulation were measured at 30, 60, and 90 days after planting. The results showed significant improvements in all growth parameters with the application of cow manure compared to the control. The best performance was observed at 300 g of cow manure per polybag, resulting in a maximum seedling height of 35.2 cm, 14.2 leaves per seedling, and a dry biomass of 34.7 g. The cow manure enhanced soil fertility, improved water retention, and supported microbial activity, contributing to better seedling vigor. In conclusion, cow manure is a viable organic amendment for cocoa seedling production, especially in resource-constrained farming systems